The Scientific Thought of Lafcadio Hearn: A Case of Interpreting Japanese Art - Nakagawa, Tomomi (Review of International American Studies, 2014)
Tomomi Nakagawa Meiji University, Japan In this session, I would like to focus on Lafcadio Hearn’s scientific thought. His absorption in Herbert Spencer is well-known; and he tries to use Spencer’s theory positively in understanding Japanese culture, especially in understanding its religions, Shinto and higher (dogmatic) Buddhism. However, I would like to focus on his vision of understanding Eastern (Japanese) art. He also tries to consider it with the aid of the scientific point of view. While Western painters try to paint a particular model precisely, Japanese painters try to make deformed or abstract works based on their own recollection and memory. In his essay ‘About Faces in Japanese Art’, Hearn refers to this deforming process. With the aid of ‘one of the living greatest naturalists’, Hearn maintains that Japanese paintings have succeeded in extracting the essence of the objects scientifically. Here he understands that both abstraction in Japanese paintings and scientific data extraction seem to share a similarity. Hearn’s lifetime was also the time of science; reliance on scientific knowledge and proof increased dramatically on an unprecedented scale. We could connect his suggestion to this contemporary social and cultural condition.